2008
DOI: 10.1210/jc.2007-0927
|View full text |Cite
|
Sign up to set email alerts
|

A Maternal Epimutation of GNAS Leads to Albright Osteodystrophy and Parathyroid Hormone Resistance

Abstract: This observation suggests that: 1) the decreased expression of Galphas due to GNAS epimutations is not restricted to the renal tubule but may affect nonimprinted tissues like bone; 2) PHP-Ib is a heterogeneous disorder that should lead to studying GNAS epigenotype in patients with PHP and no mutation in GNAS exons 1-13, regardless of their physical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 16 publications
6
54
0
Order By: Relevance
“…Recent data showed that GNAS-related disorders are more heterogeneous than previously understood. Molecular overlap between clinically diagnosed PHP-Ia and -Ib has been reported (29,30,31,32). In addition to sequencing analysis of GNAS, MS-MLPA is a powerful tool for molecular diagnosis in individual patients and provides fruitful information that will lead to a better understanding of these disorders by revealing various genetic and/or epigenetic alterations in each clinical case.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data showed that GNAS-related disorders are more heterogeneous than previously understood. Molecular overlap between clinically diagnosed PHP-Ia and -Ib has been reported (29,30,31,32). In addition to sequencing analysis of GNAS, MS-MLPA is a powerful tool for molecular diagnosis in individual patients and provides fruitful information that will lead to a better understanding of these disorders by revealing various genetic and/or epigenetic alterations in each clinical case.…”
Section: Discussionmentioning
confidence: 99%
“…PHP-Ia is associated with multiple hormone resistance, including toward parathyroid hormone (PTH) and thyroid stimulating hormone (TSH), and Albright hereditary osteodystrophy (AHO) (3)(4)(5)(6). Like with PHP-Ia, patients affected by PHP-Ib develop resistance toward PTH leading to hypocalcemia and hyperphosphatemia, which can sometimes be associated with mild resistance to TSH; unlike PHP-Ia, PHP-Ib appears to be only rarely associated with AHO features, such as shortening of metacarpals (13)(14)(15).…”
mentioning
confidence: 99%
“…Clinical diagnosis of PHP1A and PHP1B is hampered by (epi)genetic and clinical overlaps. [24][25][26][27] It is therefore of utmost importance to establish a reliable identification and quantification of the methylation at GNAS-DMRs to (i) provide an accurate diagnosis of PHP to patients and physicians, (ii) orientate genetic and cytogenetic investigations depending on the methylation pattern and (iii) identify patients without any known primary defect causing the methylation anomalies to nourish the research.…”
Section: Discussionmentioning
confidence: 99%
“…First, beyond the classic PHP type 1 classification, our groups and others demonstrated a genetic overlap between PHP1A and PHP1B, reporting patients with mild AHO features and methylation defects. [24][25][26][27] Second, Gsa activity has also been reported to be decreased not only in patients with GNAS mutations (PHP1A) but also in patients with methylation defects at the GNAS locus. 28 Third, as mentioned above, methylation defects at the GNAS locus may be partial and undetected by non-quantitative methods of methylation analysis.…”
Section: Introductionmentioning
confidence: 99%